Meibomian gland dysfunction in longstanding prosthetic eye wearers. Issue 4 (15th January 2013) - Jang, Sun Young; Lee, Sang Yeul; Yoon, Jin Sook
Abstract : Purpose: To determine whether meibomian gland dysfunction (MGD) is a possible cause of ocular discomfort in patients wearing an ocular prosthesis, with the paired normal eye used as a control. Methods: Thirty consecutive patients with a unilateral ocular prosthesis completed a questionnaire designed to identify MGD-related ocular symptoms. Both eyelids of each patient underwent slit lamp examination, meibography imaging, and Fourier-domain (FD) optical coherence tomography (OCT) scanning. Intra-individual comparison of main outcome measures between the eyelids of a prosthetic eye and paired normal eyelids was performed using Wilcoxon signed-rank test. A linear mixed model was used to investigate an association between ocular symptoms and condition of meibomian gland/tear parameters. Results: The eyelids with an ocular prosthesis exhibited significantly higher scores for ocular symptoms, lid margin abnormality, meibomian gland expression, and meibography compared to the normal eyelids (p<0.01 for all scores). Tear parameters in the eyelid of a prosthetic eye, assessed with FD OCT, were significantly lower than those of the normal eyelid (p<0.01 for all scores except tear meniscus angle). The ocular symptom score was significantly positively correlated with the meibography score and negatively correlated with tear parameters (p<0.01 for all parameters, linear mixed model). Conclusions: Compared to paired normal eyelids, the eyelids with an ocular prosthesis exhibited significant signs of MGD. These results indicate that clinical assessment and management recommendations for MGD may benefit patients with prosthetic eyes, especially those with ocular discomfort.